Few Theorems on an Extension of Bailey’s Formula Involving Product of Two Generalized Hypergeometric Functions - Paudel, Resham Prasad; Pahari, Narayan Prasad; Poudel, Madhav Prasad (Journal of Nepal Mathematical Society, 2024)
This paper presents an extensive study of the product two generalized hypergeometric functions. Particularly motivated by the papers of Kim et al. and Rakha et al., our aim of this note is to provide two interesting extensions of the well-known Bailey’s formula involving product of two generalized hypergeometric functions. The special cases of our main findings are some well-known results.